Field observations of mating behavior in the neck-banded snake Scaphiodontophis annulatus (Serpentes: Colubridae) - Sasa, Mahmood (2006)
We observed the mating behavior of the neck-banded snake Scaphiodontophis annulatus (a common species of colubrid in the South Pacific of Costa Rica) in the pre-montane wet forest of Las Cruces Biological Station (San Vito de Java, Costa Rica). Three S. annulatus were observed during courtship between 10-12 AM in a patch of primary forest. The two males were observed to interact with the female, but not signs of male-maleagonistic interactions were observed. Their behavior includes grabbing and holding the female, copula, and bitingduring the copula.